LIF Upregulates Expression of NK-1R in NHBE Cells - Cheng-Ping Hu; Jun-Tao Feng; Yu-Ling Tang; Jin-Qi Zhu; Min-Juan Lin; Ming-En Yu (Mediators of Inflammation)
Leukemia inhibitory factor (LIF), a cytokine at the interface between neurobiology and immunology, is mainly mediated through JAK/STAT pathway and MAPK/ERK pathway. Evidence suggested LIF is related to the higher expression of neurokinin-1 receptor (NK-1R) in asthma. In this study, the immunohistochemistry stain showed the expressions of NK-1R, LIF, p-STAT3, and p-ERK1/2 in the lung tissues of allergic rats were increased compared with the controls, and the main positive cell type was airway epithelial cell. Normal human bronchial epithelial cells were treated with LIF in the presence or absence of AG490 (JAK2 inhibitor), PD98059 (MEK inhibitor), and the siRNA against STAT3. Western blot and RT-PCR indicated that LIF induced the expression of NK-1R, which was inhibited by the inhibitors mentioned above. No significant interaction was found between JAK/STAT pathway and MAPK/ERK pathway. In summary, bronchial epithelial cell changes in asthma are induced by LIF which promotes the expression of NK-1R, and JAK/STAT pathway and MAPK/ERK pathway may participate in this process.